Materi Teks dalam Modul English for Beginners untuk Pembelajar Bahasa Asing di Konsultan Bahasa Denpasar - Dwi Rahayu, Ni Kadek (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2024)
This study aimed at examining the text forms and the text genres in the module English for Beginners which was used as a learning media at Language Consultant or English Foundation in Denpasar. This study used Qualitative research. The method of collecting data that is documentation and observation methods by note-taking technique. Then, the analysis which used was content analysis. The result of this study used informal method by words and sentences interpretatively. The result showed that consist of 77 (seventy-seven) text forms in the form of 53 (fifty-three) dialogue texts and 34 (thirty-four) monologue texts. Then the genre of text which appeared in this module is that 22 (twenty-two) descriptive genres and 14 (fourteen) narrative genres. The genre criteria appeared is that social function and linguistic reality which already appropriated with the criteria, however the generic structure had not fulfilled the structure criteria yet generally and tended to the structure were made in short paragraph so as the comprehension of the text were not incomplete